THE INFLUENCE OF POSITIVE PARENTING AND PARENTAL RELIGIOSITY ON CHARACTER EDUCATION AT TAWAKKAL INTEGRATED ISLAMIC ELEMENTARY SCHOOL PACITAN - Resita; Muhammad Aldin Ridloi; Anip Dwi Saputro; Nuraini (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
The abstract contains a brief description of the problems and research objectives, the methods used, and the results of the research. The pressure for writing abstracts is mainly on the results of the research (research). If in the form of written ideas, emphasize the concept and discussion. Abstract written in English. Abstract typing is done with a single space with narrower margins than the right and left margins of the main text. Keywords need to be included to describe the field of study discussed and the main terms that underlie the study. Key words can be single words or word combinations. Number of key words 3-5 words. These keywords are required for computerization. Searching for research titles and abstracts is made easy with these keywords.